Internalisasi Nilai Moderasi Beragama dan Implikasinya terhadap Sikap Toleransi Mahasiswa - Hilyah Ashoumi; Ihdina Auliya Husna; Chalimatus Sa’diyah (SAP (Susunan Artikel Pendidikan), 2023)
This research aims to describe the process of internalizing the values of religious moderation in the Aswaja course and its implications for student tolerance. This research uses qualitative methods through a phenomonological approach. The research is based on subjective or phenomenological experiences experienced by individuals, it can reveal the value of religious moderation in student tolerance. The results of this study indicated the process of internalizing religious moderation values so that student tolerance can be formed through learning planning that leads to moderate character, implementation of constructive learning, field assignments, and evaluation of processes and results. After the internalization process in the Aswaja course, students understand that there are differences in the opinions of scholars who are furu'iyyah and ushuliyah. From this understanding then arises an attitude of tolerance among fellow followers of Islam.